A brutal reckoning : Andrew Jackson, the Creek Indians, and the epic war for the American South - Cozzens, Peter 1957- (New York Alfred A. Knopf, 2023)
"From acclaimed historian Peter Cozzens, the pivotal struggle between the Creek Indians and an insatiable United States for control over the Deep South"--Provided by publisher.
From the ashes of the Entrada -- A rope of sand -- Between three fires -- The sweets of civilization -- The hungry years -- Rise of the Red Sticks -- Civil war -- Stark mad -- Terror in the Tensaw -- The emergency of Old Hickory -- Invasion of the Tennesseans -- The Red Sticks resilient -- All we lack is powder and lead -- Tennesseans to the rear -- Jackson courts disaster -- A slow, laborious slaughter -- An elusive peace -- Betrayal at Fort Jackson -- A scalp for a scalp -- Shades of genocide.
Includes bibliographical references and index.
111479
Keywords: Jackson, Andrew -- 1767-1845 -- Military leadership; 1800-1899; Creek War -- 1813-1814; Creek War -- Campaigns -- 1813-1814; Creek Indians -- Southern States -- History; Creek Indians -- Southern States -- History -- 19th century; Indians, Treatment of -- Southern States; Command of troops; Creek Indians; Indians, Treatment of; Military campaigns; Territorial expansion; History -- United States; United States -- Territorial expansion; Southern States; United States; History